Phosphorus physiological ecology and molecular mechanisms in marine phytoplankton. Issue 1 (11th January 2016) - Lin, Senjie; Litaker, Richard Wayne; Sunda, William G.
Abstract : Phosphorus (P) is an essential nutrient for marine phytoplankton and indeed all life forms. Current data show that P availability is growth‐limiting in certain marine systems and can impact algal species composition. Available P occurs in marine waters as dissolved inorganic phosphate (primarily orthophosphate [Pi]) or as a myriad of dissolved organic phosphorus (DOP) compounds. Despite numerous studies on P physiology and ecology and increasing research on genomics in marine phytoplankton, there have been few attempts to synthesize information from these different disciplines. This paper is aimed to integrate the physiological and molecular information on the acquisition, utilization, and storage of P in marine phytoplankton and the strategies used by these organisms to acclimate and adapt to variations in P availability. Where applicable, we attempt to identify gaps in our current knowledge that warrant further research and examine possible metabolic pathways that might occur in phytoplankton from well‐studied bacterial models. Physical and chemical limitations governing cellular P uptake are explored along with physiological and molecular mechanisms to adapt and acclimate to temporally and spatially varying P nutrient regimes. Topics covered include cellular Pi uptake and feedback regulation of uptake systems, enzymatic utilization of DOP, P acquisition by phagotrophy, P‐limitation of phytoplankton growth in oceanic and coastal waters, and the role of P‐limitation in regulating cell size and toxin levels in phytoplankton. Finally, we examine the role of P and other nutrients in the transition of phytoplankton communities from early succession species (diatoms) to late succession ones (e.g., dinoflagellates and haptophytes).